Current regimens and novel agents for mantle cell lymphoma. (28th June 2014) - Chen, Yiming; Wang, Michael; Romaguera, Jorge
Summary Mantle cell lymphoma is a heterogeneous subtype of non‐Hodgkin lymphoma. Conventional treatment with immunochemotherapy followed by autologous stem cell transplantation or intensive immunochemotherapy alone has improved outcomes, but the disease remains incurable. Recent advances in basic and translational research have significantly enhanced our understanding of disease pathogenesis and have sparked the development of novel therapies. Novel agents include the proteasome inhibitor bortezomib, the immunomodulatory agent lenalidomide, the phosphatidylinositol‐4, 5‐bisphosphate 3‐kinase pathway inhibitor idelalisib and the Bruton tyrosine kinase inhibitor ibrutinib. Preliminary results from clinical trials, especially from studies of ibrutinib, have proven these agents to be effective. In ongoing studies, these agents are being integrated into conventional immunochemotherapy regimens to hopefully improve patient outcomes.